„Notaty pamiętnikowe” Antoniego Łazarowicza (1819-1905) – świadectwo Polaka w „rosyjskim mundurze”: “Notaty pamiętnikowe” of Antoni Łazarowicz (1819-1905) – Pole’s testimony in the “Russian uniform” - Korybut-Marciniak, Maria (Przegląd Wschodnioeuropejski, 2020)
Memoirs “Notaty pamiętnikowe” of Antoni Łazarowicz (1819-1905), preserved in the manuscript in the Lithuanian Library of the Academy of Sciences Wróblewscy in Vilnius constitute a unique document. Their author, a civil servant in Vilnius, discovers his true attitude to the tsarist authorities in his diary. This interesting source shows the other face of a tsar official. It is also a valuable account of the living conditions of Borderland Intelligence in the 19th century.